The profiles of Muhammadiyah Student Association cadres in a disruptive era - Setiyo Budi Santoso (Universitas Muhammadiyah Magelang, 2022)
The student movement possesses strategic capital for influencing social change. In the age of disruption, social problems frequently leap far to disrupt social habits. The development of the cadre resources of the Muhammadiyah Student Association (IMM) must take into account the realities of society in the age of disruption. However, there are few publications of ideas that offer cadre development models based on the most recent social developments. The purpose of this article is to broaden the perspective on the profile of IMM cadres in the age of disruption. Six alternative profiles for the IMM cadre profile development scenario are: (1) adequate moral standards, (2) creative-collaborative through multidisciplinary innovation, (3) capable of digital literacy, (4) resilient to transformation, (5) sensitive to the diversity of social potential, and (6) effective in disseminating ideas.